Effect of Cultivars, Compost, Humic Acid and Their Interactions on Leaf Nutritional States of Sweet Cherry (prunus avium l.) - Mayi, Azad A.; Ibrahim, Nawzad J. (Science Journal of University of Zakho, 2015)
the present study was carried out on sweet cherry (Prunus avium L.), during the growing season of (2012-2013) on private sweet cherry orchard, located in the Bibad village near Amadi town / Duhok governorate- Kurdistan region-Iraq. The field experiment was done in the orchard that contained two sweet cherry cultivars (“Nefertity” and “Berlit”). The application of compost was done in December 25th 2012, at (0, 2, 4 and 6 kg /tree), foliar spray of humic acid done at (0, 100, 200 and 300 ppm) and repeated after two weeks. The results are summarized as follows: Nefertity cultivar significantly dominated over Berlit cultivar in leaf N, P content, whereas Berlit cultivar dominated leaf (N, K, Ca). Compost specially at 4kg/tree has significantly improved leaf P, K,whereas, compost at 6 kg/tree leaf nutrient N. Humic acid specially at 300 ppm has significantly increased the leaf nutrients N, P, while, 200 ppm increased the leaf K, while, 100 ppm increased the leaf N, K. The interactions between cultivars, compost and humic acid has affected significantly most of the studied parameters. The more effective treatment interactions was Nefertity + 6 Kg /tree of compost plus 200 ppm of humic acid which increased significantly P,K, but Nefertity + 6 Kg /tree of compost plus 300ppm of humic acid treatment increased leaf N content.